Percepción del desempeño ambiental en los empleados de empresas del sector construcción certificadas en ISO 14001 - Vera-Solano, Javier Augusto (2023)
The study analyzes the environmental performance and the factors that can affect it in the case of construction sector companies. For this purpose, a sample of ISO 14001 certified construction companies in the Metropolitan area of Valle de Aburrá (Medellín, Colombia) was studied. The factors analyzed included training, management participation, community involvement, knowledge of environmental regulations, communication, and employee motivation. A case study methodology, descriptive observational, and exploratory in nature, was employed. The factors under review were analyzed based on the perception of coordinators and employees of the participating companies through the use of surveys. The results indicate that management and community involvement in environmental management are factors that influence environmental performance. On the other hand, factors such as training, the level of familiarity with environmental regulations, and employee motivation, while important for maintaining the environmental management system's operation, are not considered determinants from the personnel's perspective for a company to achieve better environmental performance.